Establishment of a Non-Invasive Semi-Quantitative Bioluminescent Imaging Method for Monitoring of an Orthotopic Esophageal Cancer Mouse Model. - Shinji Kuroda (PLoS ONE, 2014)
Orthotopic models of various types of tumors are widely used in anti-tumor therapeutic experiments in preclinical studies. However, there are few ways to appropriately monitor therapeutic effect in orthotopic tumor models, especially for tumors invisible from the outside. In this study we aimed to establish a non-invasive semi-quantitative bioluminescent imaging method of monitoring an orthotopic esophageal cancer mouse model. We confirmed that the TE8 esophageal cancer cell line implanted orthotopically into the abdominal esophagus of nu/nu mice (n = 5) developed not only a main tumor at the implanted site, but also local lymph node metastases and peritoneal disseminations within 6 weeks after inoculation. We established a TE8 cell line that stably expressed the firefly luciferase gene (TE8-Luc). We showed that TE8-Luc cells implanted subcutaneously into nu/nu mice (n = 5) grew over time until 5 weeks after inoculation. Tumor volume was strongly correlated with luminescent intensity emitted from the tumor, which was quantified using the IVIS imaging system. We then showed that TE8-Luc cells implanted orthotopically into the mouse abdominal esophagus (n = 8) also formed a tumor and that the luminescent intensity of such a tumor, as detected by IVIS, increased over time until 7 weeks after inoculation and was therefore likely to reflect tumor progression. We therefore propose that this orthotopic esophageal cancer model, monitored using the non-invasive semi-quantitative IVIS imaging system, will be useful for in vivo therapeutic experiments against esophageal cancer. This experimental setting is expected to contribute to the development of novel therapeutic technologies for esophageal cancer in preclinical studies.